Decorum. Kardenia. O szalonym z "mad songu" Henry’ego Purcella - Igielska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Cardenio’s Decorum. About the madman from Henry Purcell’s mad song The central topic of the article Cardenio’s Decorum is the depiction of madness in words and music. The character of Cardenio, the betrayed and lovesick Andalusian nobleman of Miguel Cervantes Saavedra’s Don Quixote, represents one of many theatrical madmen who could be seen on the English stage during the Restoration period (1660–1700) and at the same time one of those who used to present their unusual mental condition in the frame of a stage song, the so-called ‘mad song’. The function of music consists here in the transfer of affection and vivid images: bound together with unreal visions, the music generates a kind of ‘mad’ dramaturgy, in which the images appear as an analogue for the character’s inner state and decide how the musical action is to develop.